(untitled) (Research, Society and Development, 2021)
Arbuscular mycorrhizal fungi (AMF) are known to provide plant species with several benefits, such as an increased production of bioactive compounds. However, it is yet to be defined whether extracts of mycorrhizal plants are more efficient in vitro antibacterial actions when compared to non-mycorrhizal plants. We tested the hypothesis of whether or not, methanolic extracts of Libidibia ferrea fruits, from plants established in the field and inoculated with AMF, have higher antibacterial action when inoculated with Acaulospora longula, Claroideoglomus etunicatum or Gigaspora albida. In addition, native L. ferrea fruits collected from the Caatinga area were also tested. The extracts of L. ferrea fruits inoculated with A. longula had higher in vitro antibacterial action in relation to the extracts of fruits from non-inoculated plants (p <0.05) thus characterizing the first record of different antibacterial actions of plant extracts due to inoculation with AMF. The extracts of L. ferrea fruits inoculated with A. longula were more efficient in inhibiting growth of Gram-negative bacteria. The zone diameters of inhibition ranged from 2.48 % to 7.56 % larger than the zones of the non-inoculated L. ferrea fruit extracts. The inoculation of L. ferrea with AMF may represent an alternative way of producing fruits with different antibacterial activity.